PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMBANGUN BUDAYA MUTU DI LINGKUNGAN PENDIDIKAN SDN SUNGAI SANDUNG 2 - Ahmad Farhan Nashar; Nurhalimah Sa’dah; Aslamiah, Aslamiah; Celia Cinantya (Bajang Institute, 2024)
The quality of education is one of the main issues that continues to be discussed in the world of education due to the complexity of the problem. Efforts to improve the quality of education in schools require concrete actions supported by effective principal leadership. This study aims to explore the role of principal leadership in building a culture of quality in the educational environment. The research approach uses a qualitative descriptive method with data collection through interviews, observations, and documentation studies. The results of the study indicate that principals who apply a leadership style based on ethical values ​​and organizational culture are able to create behavior, culture, and symbols in schools that support the achievement of superior education quality. In conclusion, good principal leadership is the main key to improving accountability and quality of education in schools.